A comparative approach to enhance the electrical performance of PEDOT:PSS as transparent electrode for organic solar cells. Issue 1 (January 2020) - Borazan, Ismail; Bedeloğlu, Ayşe Celik; Demir, Ali
In this article, the improvement in electrical performance of poly(3, 4-ethylenedioxythiophene)–poly(styrenesulfonate) (PEDOT:PSS) as the transparent electrode doped with different additives (ethylene glycol (EG), isopropyl alcohol) or treatment of sulfuric acid was enhanced that organic solar cells (OSCs) were produced by using poly(3-hexylthiophene-2, 5-diyl):[6, 6]-phenyl C61 butyric acid methyl ester. OSCs were fabricated by the doped or treated PEDOT:PSS films as transparent electrodes. The photoelectrical measurements were carried out and the effects of doping or treatment were compared. As a result, EG-added PEDOT:PSS electrode showed the best power conversion efficiency value of 1.87% among the PEDOT:PSS anodes.